The Effects of High Level Natural Radiation in Mamuju - Indonesia on the Immune System of Its Residents - D Darlina; T. Rahardjo; H. N. E. Surniyantoro; N. Rahajeng; M. Syaifudin (Atom Indonesia, 2022)
The immune system is one of the most significant defenses against environmental insults including natural radiation. The purpose of this preliminary study was to assess the effects of high natural radiation to Mamuju residents, by focusing on immune-related blood cell counts (leukocytes, lymphocytes, monocytes, and granulocytes) and immunoglobulin E (IgE) level. The blood samples were collected from 18 adult residents in a high background radiation area (HBRA) while 18 residents in a normal background radiation area (NBRA) served as a control group. The blood components were measured by using the hematopoietic analyzer, and IgE immune biomarker was measured with ELISA (enzyme-linked immunosorbent assay) according to standard protocols. The data showed that the level of all blood cells, except for monocytes, of residents in HBRA was higher than that of NBRA. Statistical analysis revealed that there was no significant difference (P>0.05) in the blood cell counts and IgE level in both groups and their values were within normal limits. The level of IgE in HBRA was significantly higher than the control area (P≤0.05), as its IgE level in males compared to females in both residents. The relationship between IgE level and age were negative in these residents. From this study, it was concluded that long-term exposure to high radiation may affect the immune system as one of radiation adaptive response.